INFLUENCE OF ACECLOFENAK ON THE LEVEL OF PROAND ANTIINFLAMMATORY CYTOKINES IN THE PATIENTS WITH RHEUMATOID ARTHRITIS AND CHRONIC KIDNEY DISEASE - O. Zubl; W. Roborchuks; G. Dotsyukl (Ukrainian Journal of Nephrology and Dialysis, 2015)
The purpose - to investigate the effect of aceclofenac on the level of proand anti - inflammatory cytokines in patients with rheumatoid arthritis and chronic kidney disease.Material and Methods: The research included 88patients: 45 with rheumatoid arthritis (RA) without chronic kidney disease (CKD), 43 with RA and CKD stage I without nephrotic syndrome. In a complex therapie of patients it is included nonsteroid anti - inflammatory drug aceclofenac. Influence of aceclofenac was compared with meloxicam. It is investigated to patients the content IL - 1$, IL - 10, TNFa, TGF$1, MCP - 1 is the urine with an immunofermental method.Results. After two weeks of therapy with aceclofenac was revealed reduction IL - 1$ levels (p<0,05) and urinary (p<0,05), TNFa levels (p<0,05) in patients with RA and RA with CKD. Level of pro - sclerous cytokin TGFf>1 of blood (p<0,05) and urine (p<0,001) at patients with RA with CKD is reduced. Decrease in the MCP - 1 level in blood (in 1,5 times) and in urine (in 2 times) at patients with RA and CKD is revealed.Conclusion. Application of therapy with aceclofenac for complex treatment ofpatients with RA and CKD improves efficiency of treatment for these patients through improvement cytokines of blood and urine.